Effect of cement type and thickness on push-out bond strength of fiber posts - Farzaneh Farid; Khadijeh Rostami; Sareh Habibzadeh; MohammadJavad Kharazifard (Tabriz University of Medical Sciences, 2018)
Background. This study investigated the effect of the thickness of two resin cements on push-out bond strength of fiber posts to root dentin. Methods. Sixty decoronated single-rooted teeth were endodontically treated. The specimens were then randomly allocated to two groups (n=30); group 1: drill size 90 w, matching the size of fiber posts used; group 2: drill size 110, larger than the posts. The specimens in each group were divided into 2 subgroups (n=15); subgroup SE, in which the posts were cemented with self-etch Panavia F2.0 and subgroup SA, in which self-adhesive Panavia cement was used. After 72 hours, 2 slices with 1 mm of thickness were prepared from the mid-root of each specimen. Push-out bond strength test was performed in a universal testing machine at a crosshead speed of 1 mm/min. Data were analyzed with two-way ANOVA and t-test. Results. The mean bond strengths of the posts cemented in matched-size spaces for SE and SA groups were 4.02±1.6 and 4.12±2.3 MPa, respectively. For posts cemented in oversized spaces, the values were 4.9±2.3 and 2.8±1.3 MPa, respectively. In matched-size spaces, there was no significant difference between the two groups. Conclusion. The results of this study suggested that increasing the cement thickness would reduce the bond strength of fiber posts to root dentin when self-adhesive cements are used; however, self-etch adhesives were not affected.